Conhecimento dos enfermeiros do Hospital Universitário Onofre Lopes sobre sistematização da assistência de Enfermagem - Mendes, Neyse Patricia do Nascimento (2010)
Nursing as a profession goes in search on quality of their care through new frameworks, trying to break postures of the health care system so fragmented in the care. To change professional practices, it is necessary to build their own knowledge grounded on Nursing Care System. The aim of this study was to analyze the influence of nurses' knowledge on care systematization in nursing in the University Hospital Natal-RN. It is an analytical descriptive study carried out at the Onofre Lopes University Hospital (HUOL), Natal-RN, 2010, the sample was composed of 40 active nurses working in hospitalization units of the hospital, the inclusion criteria were being in the monthly scale sector and agree to participate in the study. The non-participant observation and another interview were used for collecting data, statistical analysis was descriptive and inferential with reliability test, Pearson test, chi-square and Fischer, the variables that correlated were analyzed in a model Multiple logistic , calculating odds ratio. The results were: predominance of female professionals (90%), predominantly in the age range 39-46 years (37.5%), nurses who have the undergraduate degree at the Federal University of Rio Grande do Norte (80%), and who have expertise training as a minimal degree (62.5%). Among the surveyed, the knowledge showed significance with the graduation time (p = 0.018) and time working in HUOL (p = 0.036). The majority of the professionals surveyed do not know which organ is responsible for the SAE legislation (52.5%), aware of the steps needed to build the nursing diagnosis (92.5%), understand the characteristics of nursing planning (90% ). However the same professionals do not perform physical examination in patients (50.0%) did not classify the clinical findings (68.4%), and identify the problems encountered as a classification (13.2%). The planning of nursing care is carried out by verbal order of nurses (82.5%), 41% of the professionals assess only the intervention stage, in other words, the actions taken. Regarding the practical application of nursing records 53% of nurses do not realize records, 30.8% is incomplete, the other held notes (p = 0.003). The nurses know the nursing process (90% of appropriate responses), despite the actions defined by the theory are not applied in practice. Investigators believe the condition of the hospital teacher (22.5%) could positively affect the implementation of the SAE associated with the interest of professionals (20%). Of the respondents, 17.5% accept as truth the lack of facilities to assist the SAE implementation in the hospital. It was concluded that nurses know the theory that underlies the SAE and the nursing process, but do not develop the service know as well, there is need for action to boost the SAE implementation as practice of nurses in the hospital investigated